2016
DOI: 10.1038/srep23637
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles of autistic and alexithymic traits in utilitarian moral judgments in adults with autism

Abstract: This study investigated hypothetical moral choices in adults with high-functioning autism and the role of empathy and alexithymia in such choices. We used a highly emotionally salient moral dilemma task to investigate autistics’ hypothetical moral evaluations about personally carrying out harmful utilitarian behaviours aimed at maximizing welfare. Results showed that they exhibited a normal pattern of moral judgments despite the deficits in social cognition and emotional processing. Further analyses revealed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 129 publications
(261 reference statements)
1
46
0
Order By: Relevance
“…Empathy or other emotional difficulties are associated with ASD, but recent work has suggested that many of these effects are due to comorbid alexithymia4546. As a next step, the relationship between the alexithymia and moral judgement should be further explored1936. Second, the diagnoses were not obtained using the Autism Diagnostic Interview – Revised (ADI-R)47 or the Autism Diagnostic Observation Schedule (ADOS)48.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empathy or other emotional difficulties are associated with ASD, but recent work has suggested that many of these effects are due to comorbid alexithymia4546. As a next step, the relationship between the alexithymia and moral judgement should be further explored1936. Second, the diagnoses were not obtained using the Autism Diagnostic Interview – Revised (ADI-R)47 or the Autism Diagnostic Observation Schedule (ADOS)48.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that individuals with ASD who have comorbid alexithymia are atypical in terms of recognizing their own emotions1314 and in empathizing with others151617. Empathy is a social emotion that plays a crucial role in such moral evaluations, because empathy allows moral judges to understand suffering and to use the resulting “gut-feelings” to either approve or disapprove of moral actions1819.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While historically research suggests that ASD is associated with utilitarian moral judgment (Gleichgerrcht et al , 2013), a more recent study finds that the high levels of utilitarian responding, often observed in individuals on the autism spectrum, may in fact be due to the high co-occurrence of alexithymea (the inability to recognize and identify emotions) and autism. In fact, when measuring alexithymea and autistic traits separately in individuals with ASD, autistic traits are significantly negatively associated with utilitarian responses to moral dilemmas (Patil et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Past research shows that the activation of this network plays a role in promoting prosocial action aimed at alleviating victim suffering [36][37][38][39][40] . Yet, at the neural level, it has not previously been associated with the moral condemnation of those who cause others to suffer 41 .…”
mentioning
confidence: 99%